2021
DOI: 10.1111/1755-0998.13479
|View full text |Cite
|
Sign up to set email alerts
|

Testing genome skimming for species discrimination in the large and taxonomically difficult genus Rhododendron

Abstract: Standard plant DNA barcodes based on 2–3 plastid regions, and nrDNA ITS show variable levels of resolution, and fail to discriminate among species in many plant groups. Genome skimming to recover complete plastid genome sequences and nrDNA arrays has been proposed as a solution to address these resolution limitations. However, few studies have empirically tested what gains are achieved in practice. Of particular interest is whether adding substantially more plastid and nrDNA characters will lead to an increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
66
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 83 publications
3
66
0
Order By: Relevance
“…Our species discrimination results indicated that the complete plastome can provide more variation to discriminate Cephalotaxus species compared to the standard barcodes, which has also been demonstrated in other studies (e.g., Ji et al, 2020 ; Song et al, 2020 ; Fu et al, 2022 ). In addition, the complete plastome approach based on genome skimming can circumvent issues of locus choice, and low PCR and sequencing recovery rate, which are sometimes encountered in standard DNA barcoding studies ( Ruhsam et al, 2015 ; Curci et al, 2016 ).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our species discrimination results indicated that the complete plastome can provide more variation to discriminate Cephalotaxus species compared to the standard barcodes, which has also been demonstrated in other studies (e.g., Ji et al, 2020 ; Song et al, 2020 ; Fu et al, 2022 ). In addition, the complete plastome approach based on genome skimming can circumvent issues of locus choice, and low PCR and sequencing recovery rate, which are sometimes encountered in standard DNA barcoding studies ( Ruhsam et al, 2015 ; Curci et al, 2016 ).…”
Section: Discussionsupporting
confidence: 87%
“…The inclusion of multiple individuals from a single species sampled is highly important to confirm species delimitation successfully and accurately ( Liu et al, 2012 ; Fu et al, 2022 ). Therefore, in this study, all species/varieties of Cephalotaxus had more than one individual included (two to five individuals per taxon).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although genome skimming approaches, such as those implemented here, can provide crucial genome-scale data [ 48 , 75 , 76 ], more cost- and time-efficient methods, such as target enrichment sequencing [ 77 , 78 ] or restriction-site associated sequencing (RADseq) [ 26 , 47 , 79 ] might be more appropriate for this clade given the high number of samples that will likely need to be included. Ultimately, genome-scale data can also be used to reconstruct a robust phylogeny for this group to explore additional evolutionary, phylogeographic, and taxonomic questions.…”
Section: Discussionmentioning
confidence: 99%
“…With next-generation DNA sequencing (NGS) technologies, genome-wide sequence variation has begun to replace one or a few sequence loci for the identification and delimitation of plant species ( Li et al, 2015 ; Coissac et al, 2016 ; Hollingsworth et al, 2016 ). The genome skimming approach, which uses NGS technologies to generate multi-copy and highly repetitive genome components, such as whole plastid genomes (plastomes) and nuclear ribosomal DNA (nrDNA) clusters via relatively low coverage genome sequencing ( Straub et al, 2012 ), has been increasingly used for species identification and delimitation in recent years ( Nock et al, 2011 ; Kane et al, 2012 ; Dodsworth, 2015 ; Li et al, 2015 ; Ruhsam et al, 2015 ; Firetti et al, 2017 ; Fu et al, 2019 , 2021 ; Ji et al, 2019a , 2020 , 2021 ; Knope et al, 2020 ; Ślipiko et al, 2020 ; Su et al, 2021 ). Compared with restriction-site associated DNA sequencing (RAD-seq; Miller et al, 2007 ; Baird et al, 2008 ), another NSG-based technique that is extensively used to generate genomic data for plant species identification and delimitation (e.g., Wu et al, 2018 ; Donkpegan et al, 2020 ; Ma et al, 2020 ; Zhou et al, 2020 ; Li et al, 2021 ), the promising advantage of using genome skimming for species identification and delimitation is the avoidance of problems encountered with RAD-seq ( Kane et al, 2012 ; Hollingsworth et al, 2016 ), such as only applying to diploids and generating asymmetric data between distinctly related taxa.…”
Section: Introductionmentioning
confidence: 99%